Major surgery in south India: a retrospective audit of hospital claim data from a large community health insurance programme. (27th April 2015) - Shaikh, Maaz; Woodward, Mark; Rahimi, Kazem; Patel, Anushka; Rath, Santosh; MacMahon, Stephen; Jha, Vivekanand
Abstract: Background: Information about use of major surgery in India is scarce. This study aims to bridge this gap by auditing hospital claims from the Rajiv Aarogyasri Community Health Insurance Scheme (RACHIS) that provides access to free tertiary care for major surgery through state-funded insurance to 68 million beneficiaries with limited household incomes—81% of population in states of Telangana and Andhra Pradesh (combined Human Development Index 0·485). Beneficiary households receive an annual coverage of INR 200 000 (US$3333) for admissions to any empanelled public or private hospital. Methods: Publicly available deidentified hospital claim data for all surgical procedures conducted between mid-2008 and mid-2012 were compiled across all 23 districts in Telangana and Andhra Pradesh. Findings: 677 332 surgical admissions (80% at private hospitals) were recorded at a mean annual rate of 259 per 100 000 beneficiaries (95% CI 235–283), excluding cataract and caesarean sections as these were not covered under the insurance programme. Men accounted for 56% of admissions. Injury was the most common cause for surgical admission (185 733; 27%) with surgical correction of long bone fractures being the most common procedure (144 997; 20%) identified in the audit. Diseases of digestive (110 922; 16%), genitourinary (82 505; 12%), and musculoskeletal system (70 053; 10%) were other leading causes for surgical admissions. Most hospital bed-days were used for injuries (584 days per 100 000 person years; 31%), digestive diseases (314 days; 17%), and musculoskeletal system (207 days; 11%), costing 19% (INR 4·4 billion), 13% (3·03 billion), and 11% (2·5 billion) of claims, respectively. Cardiovascular surgeries (53 023; 8%) alone accounted for 21% (INR 4·9 billion) of cost. Annual per capita cost of surgical claims was US$1·49 (95% CI 1·32–1·65). Interpretation: Our findings are limited to a population socioeconomically representative of India and other countries with low-income and middle-income. Despite near universal access for major surgery, use continues to remain low, at levels expected in countries with per capita health expenditure below US$100, and lower than a tenth of rates estimated at spending (US$400–1000) comparable with financial access provided. Hence, strategies beyond traditional financing for care are required to improve use of surgery in LMICs. Funding: The George Institute for Global Health.